Use of heart rate monitors to measure heart rate variability at rest: a literature review (Research, Society and Development, 2021)
The Heart Rate Variability (HRV) is a non-invasive method to estimate the cardiac autonomic control that can be measured through the electrocardiogram (ECG), the gold standard method. Portable devices that are more practical and cheaper than ECG, such as heart rate monitors, are a more convenient alternative for measuring HRV in clinical practice, but it is necessary that their results be validated in different populations. Objective: To analyze the studies carried out on the validity of heart rate monitors in comparison with the ECG for measuring HRV at rest in different populations. Methodology: This is a literature review where studies published in the Pubmed and Scielo databases were used, no lower limit of the publication date until the year 2021. The following descriptors were used in English and Portuguese: "heart rate variability" or "cardiac autonomic control" or "Electrocardiography" or "Heart Rate", being associated with the terms "heart rate monitor" and "reproducibility" or "validity" or "agreement". Results and discussion: Fifteen studies were found that evaluated the validity of different models of heart rate monitors for measuring HRV at rest, compared to ECG, in different populations (healthy adults, athletes, elderly, children, obese adolescents, individuals with injuries spinal cord and elderly), as well as its reliability in the test-retest of some devices. Conclusion: Studies have shown that different heart rate monitor models can be used as an alternative to ECG for measuring HRV, even in different populations.